Health effects of wind turbines in working environments - a scoping review - Alice Freiberg; Christiane Schefter; Maria Girbig; Vanise Cleto Murta; Andreas Seidler (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVES: The wind industry is a growing economic sector, yet there is no overview summarizing all exposures emanating from wind turbines throughout their life cycle that may pose a risk for workers` health. The aim of this scoping review was to survey and outline the body of evidence around the health effects of wind turbines in working environments in order to identify research gaps and to highlight the need for further research. METHODS: A scoping review with a transparent and systematic procedure was conducted using a comprehensive search strategy. Two independent reviewers conducted most of the review steps. RESULTS: Twenty articles of varying methodical quality were included. Our findings of the included studies indicate that substances used in rotor blade manufacture (epoxy resin and styrene) cause skin disorders, and respectively, respiratory ailments and eye complaints; exposure to onshore wind turbine noise leads to annoyance, sleep disorders, and lowered general health; finally working in the wind industry is associated with a considerable accident rate, resulting in injuries or fatalities. CONCLUSIONS: Due to the different work activities during the life cycle of a wind turbine and the distinction between on- and offshore work, there are no specific overall health effects of working in the wind sector. Previous research has primarily focused on evaluating the effects of working in the wind industry on skin disorders, accidents, and noise consequences. There is a need for further research, particularly in studying the effect of wind turbine work on psychological and musculoskeletal disorders, work-related injury and accident rates, and health outcomes in later life cycle phases.